PENGARUH KOREKSI FISKAL PAJAK PENGHASILAN BADAN & PPh PASAL 23 LAPORAN KOMERSIAL TERHADAP LAPORAN KEUANGAN FISKAL - Jaya, Hendry (MEASUREMENT : Jurnal Program Studi Akuntansi, 2015)
The purpose of this study was to determine the value of income tax payable by the company ,with reconciling commercial financial statements to the fiscal financial ststements. By doing reconcilition, company did not need to create two bookkeping for different puposes. The company just made corrections to items that were not in accordance, a negative corretion would decrease taxable income. The result of study concluded that there are differences the value of profit and loss according to the commercial and the fiscal .It occurs because the fiscal correction on the cost and income  in the commercial financial statements based on tax regulations.  Keywords :      Income Tax, Commercial Finacial Statement, Fiscal Financial Statement, Fiscal Correction.